Thinking of Autonomy as Automatism: the Case of Autonomy in Thucydides’ History - Gerolemou, Maria (Araucaria, 2017)
The following article engages in an attempt to review and further explore the notion of autonomy in Thucydides, which is described by scholars as different from freedom, eleutheria, and as primarily assigned to the interests of a weaker state that is trying to exert its independence. Without rejecting the relational aspect of the notion of autonomy, the article argues further on autonomy’s internal aspect, ultimately trying to prove how autonomy in Thucydides is moreover presented as an automatic habit and a behavioral pattern that reflects a restrictive, political and artificial perspective of external superior powers.